Redesign of a polystyrene packaging process for a distribution center: Case study of the productive logistics sector in Cartagena de Indias, Colombia (LACCEI, 2024)
The present study aims to improve the efficiency of polystyrene packaging processes through the implementation of a new design ofthe packaging machine for a distribution center in the manufacturing sector of the city of Cartagena. Initially, a diagnosis of the current situation ofthe polystyrene packaging process was made, in order to determine what are the reasons or causes that affect the storage process, since thedemand required by customers is currently not met. Secondly, an analysis is proposed using different work methodologies such as staticanalysis, the Ishikawa method, Value Stream Mapping and the financial one to determine the causes of the problem and the feasibility of theproject. In order to provide a solution to the problems identified in this research case, the implementation of one of the 3 alternatives exposed asa result of the investigation is proposed, taking as a reference the delay time in operations, times of use, necks of bottle, equipment capacitiesand the costs associated with non-compliance.